The comparison between combination of candesartan-amlodipine and candesartan-furosemide on blood pressure in hypertensive patients with chronic kidney disease - Fitri Rachmaini; Dian Ayu Juwita; Almahdy A; Rahmad Abdillah; Yolanda Mayestika Wati (Pharmaciana, 2022)
Chronic renal disease is significantly increased by hypertension. Controlling blood pressure is critical in hypertensive individuals. Patients who have good blood pressure (BP) control can reduce morbidity and mortality. This study aimed to compare blood pressure reduction of candesartan-amlodipine with the candesartan-furosemide combination in hypertensive patients with chronic renal disease. The study was conducted by a cohort study design. Retrieval of medical record data was carried out prospectively during the period February-April 2019. The blood pressure reduction was assessed by changes in mean systolic and mean diastolic blood pressure and mean diastolic blood pressure and was analyzed statistically with the SPSS program. A total of 54 patients met the inclusion criteria, consisting of 27 patients receiving candesartan-amlodipine combination and 27 patients receiving candesartan-furosemide combination therapy. The results of the sociodemographic characteristics patients were male 30 patients (55.6%), age 56-65 years 24 patients (44.4%), senior high school education level 31 patients (57.4%). Candesartan-amlodipine and candesartan-furosemide combinations both decreased blood pressure in patients. However, the result of the statistical analysis revealed that there was no significant difference in blood pressure decline. (p> 0.05) between the two combinations.